Governance Pemekaran Desa dalam Perspektif Politik Lokal: studi kasus Pembentukan Desa Lewouran di Kabupaten Flores Timur - Oyan, Maria Regina Tapo; Muhammad, Adji Suradji (Jurnal Ragam Pengabdian, 2026)
Village expansion is a public policy that is shaped not only by administrative requirements but also by governance dynamics and local political processes involving multiple stakeholders. This study aims to analyze the governance of the establishment of Lewouran Village from the perspective of local politics by examining the patterns of interaction, negotiation, and power relations among actors involved in the village expansion process. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis involving village government officials, sub-district authorities, customary leaders, community leaders, the village expansion committee, and local residents. Data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the governance of Lewouran Village expansion was constructed through dynamic interactions between formal and informal actors. Community aspirations emerged as the primary driving force behind the expansion process, followed by negotiations with the village government, the establishment of an expansion committee, and the legitimization of the process through customary institutions. Furthermore, the process was characterized by competing interests, institutional co-optation, and adaptive strategies to fulfill administrative requirements. The study concludes that the success of village expansion depends not only on regulatory compliance but also on the capacity of stakeholders to develop collaborative governance that integrates the interests of local communities, village authorities, and customary institutions. This study contributes to the literature on village governance by highlighting the strategic role of collaboration between formal and informal institutions in shaping new village governance.